O col??gio comercial Visconde de Cair?? (1954-2002) ??? o ensino profissional que impulsionou trajet??rias - Gaidargi, Alessandra Maria Martins (2018)
This thesis focuses on the history of the Col??gio Comercial Visconde de Cairu, in the historical section from 1954 to 2002, which corresponds to its period of operation. Established in the city of S??o Paulo, in the district of Belenzinho, this educational institution has undergone several phases of the Brazilian educational history, and a series of legislative changes, being its trajectory remarkable in the evolutionary process of commercial education in Brazil. Transitions of nomenclature of the courses, since commercial secondary education to high school technical education, synthesize the period of greater development of vocational training for tertiary education, and the history of the institution presented here illustrates these changes and their influence on Brazilian middle-level education up to the present days. This study also provides a brief account of the general history of commercial education in Brazil and the main legislative interventions that took place, and draws parallels between the development of this segment of education and the concepts of Escola Nova, epistemology of Jean Piaget, and guidelines drawn by International Labor Organization for vocational education. The trajectories of leaders, teachers and students who participated actively in the history of this school institution - in various periods within the proposed historical section - also integrate this work, which proposes to study the whole from particularities with a referential approach of the Marxist investigative dialectic.